Flood Detection Tool Using Ultrasonic Sensor Based on Telegram and Sound in Krueng Kluet River Flow - Ilham, Dirja Nur; Candra, Rudi Arif; Fardiansyah, Fardiansyah; Sipahutar , Erwinsyah; Budiansyah, Arie (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2024)
Flooding is a problem that until now still requires special handling from various parties, both from the government and the community. Flooding is not a light problem because flooding can disrupt community activities and cause losses, such as the washing away of household equipment, valuables, and electronic goods. Flooding occurs due to rising water levels in rivers due to abnormal rainfall, damaged dams, obstruction of water flow at the site of the dam's destruction in the River Basin Area (DAK), and the construction of facilities and infrastructure. The series of